Uncertainty analysis of the strength capacity and failure path for a transmission tower under a wind load. Issue 173 (February 2018) - Fu, Xing; Li, Hong-Nan
Abstract: Many tower structures have collapsed during strong wind events; therefore, the objective of the present study is to estimate the strength capacity of transmission towers accurately and to identify all potential failure modes. An uncertainty analysis method for tower structures subjected to a wind load is presented. Subsequently, random samples of material properties and section dimensions are generated based on the Latin Hypercube Sampling technique and then used to establish uncertain finite element models for transmission towers. A static non-linear buckling analysis for structures subjected to a wind load is conducted using ANSYS software. Based on tower models incorporating uncertainty, our analysis reveals that there are six possible initial failure tower members but only one for the deterministic model, indicating that the uncertainties regarding material properties and section dimensions should be taken into account. Furthermore, a sensitivity analysis is conducted, and the results reveal that the uncertainty of material properties has a stronger influence than the uncertainty of section dimensions. Finally, the influence of wind attack angle is discussed, and the initial failure positions and corresponding probabilities for various wind attack angles are obtained. The results show that the most unfavorable wind attack angle is 0° and that the most probable failure position of the tower of interest is the middle of the tower body. Highlights: An uncertainty analysis method for tower structures subjected to a wind load is presented. The failure position of highest likelihood for the employed tower is the middle of the tower body. The uncertainty of material properties has a stronger influence than the uncertainty of section dimensions.